PANDANGAN FUQAHA DALAM PERNIKAHAN YANG TIDAK DIPUBLIKASIKAN - adri anto (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2024)
AbstractHikmah at tasyri’ which can be understood in order to maintain the strength of the marriage bond fraudulent actions by one of the parties then the marriage must be attended by guardian and witness even in order to strengthen the existence of two witnesses prophet once advised friends to announce their marriage which was done by throwing a party This research uses qualitative approach with library research The research results show unwitnessed and unpublicized marriages and not recorded is not allowed and a marriage witnessed by both witnesses but witnesses was ordered to be punished makruh there is Umar RA, Urwah, Abdullah ibn Ubaidillah, Ibnu Utbah, Sa’bi dan Nafi’ sahaya Ibnu Umar. Meanwhile, among the para Tabi’in is Abu Hanifah, Syafi’i dan Ibnu Munzir. And law of witnesses and publicize in marriage is sunah